Extraction of Natural Dye using Peels of Citrus Fruits for Enhancing Color Fastness of Fabrics - Farea Noor; Mehreen Ijaz (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
The current study investigates the extraction of dyestuff using citrus fruits and assesses its color, light, rubbing, and perspiration fastness. For the experimental study, three types of citrus fruits—orange, lemon, and grapefruit—were chosen to extract dye from their peels. The dye was applied to two types of fabrics (100% cotton and a blended fabric made of polyester-cotton (PC) with a ratio of 50:50) using the conventional aqueous method. The results revealed the remarkable efficacy of orange dye on both fabric types, demonstrating excellent color fastness attributes, with a minor preference for PC fabric in washing fastness. In contrast, lemon dye displayed better washing fastness properties on the tested materials as well as considerable staining potential. Grapefruit dye performed exceptionally well in terms of water and perspiration fastness. Future research could focus on improving dye extraction techniques for citrus fruits to increase color absorption and penetration. Determining various solvents, time duration for dyeing, and temperature settings could enhance the dyeing performance and effectiveness of natural dyes in different industrial applications. Further studies could also conduct life cycle assessments to measure the environmental impact of using citrus peels as a natural dye source compared to synthetic dyes in the textile industry.